The Effect Of A Training Program On Reducing The Distraction And Hyperactivity In The Primary School Stage (Journal of the College of Basic Education, 2024)
The main purpose of this study is to examine the effect of a training program to reduce distraction and hyperactivity in the primary school stage. According to this study, two hypotheses were developed, the first deals with the variable of attention distraction, and the second hypothesis deals with the variable of hyperactivity for both the experimental and control groups. The research sample consisted of (73) students. Students were divided into two groups; one is an experimental and the other is a control group. A scale was prepared to measure hyperactivity and a scale to measure distraction among students, in addition, a training program was built to be applied by teachers in the school that includes the experimental group. The validity and stability of the scale and the validity of the program were verified by presenting them to experts specialized in educational psychology, The results showed that there was a significant effect of the program on reducing the distraction and hyperactivity in the primary school stage. This study provided a number of recommendations and proposals needed for a positive effect of training program on reducing the distraction and hyperactivity in the primary school stage.